Recount Text in SFL Perspective: Pedagogical Implication based on Student’s Writing Analysis - Cakrawati, Laxmi Mustika (Register Journal, 2018)
AbstractRecount can be considered as one of the easiest types of text that can be written by students. This might be the reason why the text is learned in both junior and senior high school level. However, there are still a lot of students who cannot produce the text well. This study was aimed to analyze student’s recount text based on three metafunctions in SFL perspective. It is expected that by identifying students’ problems, teachers can decide and design appropriate pedagogical plan. The result of the study reveals that the student’s major problems in producing recount text are the use of subject and verb tense (interpersonal metafunctions), the generic structure of the text, the use of conjunctions, the grammatical errors, and L1 interference. Therefore, considering the problems found in the student’s recount text, POWER strategy is proposed as one of strategies can be applied by teachers in teaching writing, particularly teaching recount text. Keywords: recount text, systemic functional linguistics, metafunction, POWER strategy